Endoscopic transsphenoidal surgery for non-functioning pituitary adenoma: Learning curve and surgical results in a prospective series during initial experience - Boetto, Julien; Joitescu, Irina; Raingeard, Isabelle; Ng, Sam; Le Corre, Marine; Lonjon, Nicolas; Crampette, Louis; Favier, Valentin (Frontiers in Surgery, 2022)
BACKGROUND To report the initial experience of surgery for non-functioning pituitary adenoma (NFPA) from a neurosurgeon in a dedicated residency training endoscopic transsphenoidal (ETS) program, and detail the surgical and clinical outcomes during this period. METHODS A prospective series of all patients operated for NFPA, using an ETS approach, during the three first years of experience of a newly board-certified neurosurgeon was analysed. Clinical, radiological and peri-operative data were collected. Extent of resection (EOR) was determined by formal volumetric analysis. Impact of the learning curve and predictive factors of gross total resection (GTR) were determined. RESULTS Fifty-three patients with NFPA were included in this prospective cohort which was divided in two periods of time (“First period”: 30 first cases, and “second period”: 23 following cases). Baseline characteristics of the patients in the two periods were similar. Overall occurrence of complication was 22% and was not significantly different in the two periods of time. No patient had severe neurological complication. Gross total resection was achieved in 70% of patients. Mean Extent of resection was 96%. In a multiple linear regression model, a higher EOR was positively correlated with experience (p=0.018) and negatively correlated with Knosp Score equal to 4 (p<0.001). Predictive factors for GTR were Higher Knosp grade (p=0,01), higher pre-operative volume (p=0.03), and second period of time (p=0.01). CONCLUSION NFPA surgery can be safe and efficient during the learning period. Dedicated intensive learning, careful patient selection and multidisciplinary work are key to shorten the learning curve and achieve satisfactory results.